An Unusual Position of Retromandibular Vein in Relation to Facial Nerve: A Rare Case Report - Nabin Lageju; Prabhat Chandra Thakur; Pravin Kumar Jaiswal (Case Reports in Otolaryngology)
Knowledge of different anatomical structures is very important in parotid surgery to preserve facial nerve. Retromandibular vein is one of the landmarks used to identify facial nerve. So, the relation of the vein with facial nerve is very important in parotid surgery. The typical position of RMV is deep to facial nerve in almost 88% of cases reported in various literatures. Here, we present an unusual position of RMV found during parotid surgery for pleomorphic adenoma.